Sex trafficking : inside the business of modern slavery - Kara, Siddharth (New York : Columbia University Press, 2009)
"Every year, millions of women and children are abducted, deceived, seduced, or sold into forced prostitution, made to service hundreds if not thousands of men before being discarded. Generating huge profits for their exploiters, sex slaves form the backbone of one of the world's most profitable illicit enterprises, for unlike narcotics, which must be grown, harvested, refined, and packaged, the female body requires no such "processing" and can be repeatedly consumed." "In this first-of-its-kind journey, Siddharth Kara investigates the mechanics of the global sex trafficking business across four continents and takes stock of its devastating human toll. Since first encountering the horrors of sexual slavery in a Bosnian refugee camp in 1995, Kara has taken multiple research trips to India, Nepal, Burma, Thailand, Vietnam, the United Kingdom, Italy, the Netherlands, Albania, Moldova, Mexico, and the United States. He has met hundreds of slaves, has witnessed the sale of numerous human beings into slavery, and has confronted some of the criminals who have exploited them." "Drawing on his background in finance and economics, Kara provides a rare business analysis of sex trafficking, focusing on the local drivers and global macroeconomic trends that gave rise to the industry after the fall of the Berlin Wall. He quantifies the size, growth, and profitability of sex trafficking and other forms of modern slavery - metrics that have never been published before - and locates the sectors that would be hardest hit by specifically designed interventions and penalties.".
"Kara supplements his analysis with a riveting account of this unconscionable industry, sharing the moving stories of victims and revealing the shocking conditions of their exploitation. He concludes with a proposal for aggressive measures that target the essential business and economic functioning of the sex trafficking industry designed to provide a more effective global approach to abolishing these crimes against the world's most vulnerable and exploited persons."--BOOK JACKET.
Sex trafficking : an overview -- India and Nepal -- Italy and western Europe -- Moldova and the former Soviet Union -- Albania and the Balkans -- Thailand and the Mekong subregion -- The United States -- A framework for abolition : risk and demand.
"A Caravan book"--T.p. verso.
Includes bibliographical references (p. [279]-283) and index.
Also issued online
Keywords: Human trafficking; Human trafficking -- Prevention; Minorities -- Crimes against; Minorities -- Social conditions; Minorities -- Economic conditions; Globalization -- Economic conditions; Prostitution; Slavery; Sex industry